2007
DOI: 10.1021/la062900k
|View full text |Cite
|
Sign up to set email alerts
|

NMR and IR Study of Fluorobenzene and Hexafluorobenzene Adsorbed on Alumina

Abstract: The adsorption of fluorobenzene (C6H5F) and hexafluorobenzene (C6F6) onto the surface of neutral alumina is investigated by reflectance IR spectroscopy, near-IR spectroscopy, and measurement of 19F NMR chemical shift values. Chemical shifts are dependent on surface coverage and reveal multiple peaks where different adsorption environments occur. C6H5F appears to be adsorbed through polar interactions with surface hydroxyls, whereas C6F6 shows separate resonances for the first layer of coverage and outer layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…2 and 3). These broadly fall into the categories of aromatic (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), aliphatic (18-30), Hydrogen Bond Donor (HBD, 31-34) and Hydrogen Bond Acceptor (HBA, 35-37). Different isomers were used where available to exclude specific geometry effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3). These broadly fall into the categories of aromatic (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), aliphatic (18-30), Hydrogen Bond Donor (HBD, 31-34) and Hydrogen Bond Acceptor (HBA, 35-37). Different isomers were used where available to exclude specific geometry effects.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of these compounds to protic surfaces gives an opportunity to generate a parameter that describes the surface H-bond donor ability. The differences between the measured chemical shifts, and those predicted from eqn (10) were calculated (d HBD ), and an average value taken ( d HBD , Table 1). Although other reporter molecules may hypothetically become involved in similar polar interactions, the monofluoroalkanes appear the most sensitive to their environment, presumably because the interaction occurs directly through the fluorine atom under study.…”
Section: Investigation Of the H-bond Donor And Acceptor Abilities Of ...mentioning
confidence: 99%
“…Although these techniques are accurate, they have several disadvantages including the need for the expensive equipment, high cost operations and well-controlled experimental conditions. For these reasons, the most favorable technique is sorbents adsorption [7][8][9] . A widely used sorbents is silica, and it has been applied for the adsorption of styryl pyridinium dyes and several organic compounds 10-12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, silicon nitride substrates with a lower oxygen content (non-plasma treated, see SI) also revealed monolayer formation. 19 F solid-state nuclear magnetic resonance spectroscopy (ssNMR) was employed to gather further highly sensitive technique [23][24][25][26][27] to provide evidence of halogen-bonding of I-PFC12 to SiNx. 23 Figure 2d shows the ssNMR spectra of pure I-PFC12 and a I-PFC12 self-assembled monolayer adsorbed to SiNx nanoparticles.…”
mentioning
confidence: 99%
“…10,23,27 The simultaneous occurrence of the following features provides strong evidence for halogen bonding: i) the large upfield shift of the CF2 groups bound to the iodine atom (I-CF2, Δδ = -6.2 ppm) and the 2.1 ppm shift of the α-CF2; ii) the upfield chemical shifts of the terminal CF3 group (Δδ = 2.4 ppm); iii) the line width narrowing of the terminal CF3 peak, which suggests an increased mobility at the monolayer/a ir interface with respect to the other fluorine groups; iv) the line width broadening of the main CF2 backbone which suggests a reduced chain mobility due to adsorption onto the solid surface, and packing together. [24][25][26][27] The XPS and the ssNMR analysis demonstrate that I-PFC12 molecules are adsorbed to SiNx through halogen bonding, forming a uniform organic layer (see also the atomic force microscopy images in the SI). Further evidence on the nature of the interaction came from solution state 19 F NMR analysis of washings of the functionalised silicon nitride microparticles, which returned the IPFC12 unchanged and demonstrated that the interaction is non-covalent and occurs only for molecules that contain a termina l iodine atom.…”
mentioning
confidence: 99%